If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5x + 12) + -20x = -3(4x + 4) + 12 Reorder the terms: 5(12 + 5x) + -20x = -3(4x + 4) + 12 (12 * 5 + 5x * 5) + -20x = -3(4x + 4) + 12 (60 + 25x) + -20x = -3(4x + 4) + 12 Combine like terms: 25x + -20x = 5x 60 + 5x = -3(4x + 4) + 12 Reorder the terms: 60 + 5x = -3(4 + 4x) + 12 60 + 5x = (4 * -3 + 4x * -3) + 12 60 + 5x = (-12 + -12x) + 12 Reorder the terms: 60 + 5x = -12 + 12 + -12x Combine like terms: -12 + 12 = 0 60 + 5x = 0 + -12x 60 + 5x = -12x Solving 60 + 5x = -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 60 + 5x + 12x = -12x + 12x Combine like terms: 5x + 12x = 17x 60 + 17x = -12x + 12x Combine like terms: -12x + 12x = 0 60 + 17x = 0 Add '-60' to each side of the equation. 60 + -60 + 17x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 17x = 0 + -60 17x = 0 + -60 Combine like terms: 0 + -60 = -60 17x = -60 Divide each side by '17'. x = -3.529411765 Simplifying x = -3.529411765
| 9y+6x=3x-18 | | 3ln(9x)+3=12 | | 8x+62=10(x+5) | | 1/2x^2⚌6x-20 | | 180/x=15(12) | | 6x+10y=-16 | | 5(2x-2)-3=5(x-2)+7 | | 2*2*2*2*1.5*1.4=x | | 7x-(4x+5)=5x-19 | | f(x)=(-7x^2)+56x-22 | | 54+n=54 | | 40x^2-24x+25=0 | | x/6=12.4 | | 4y-4=15y+29 | | 6(x+2)=4(x+1)-6 | | 6x=y+5 | | X-1+9=3x-6 | | 1.45^1/2 | | F(t)=(1.45)^t/2 | | -3.7x=12.4 | | -26+9+y=-2+11 | | 7=4-a | | 8x+62=10+x+5 | | 4(4-d)-26=26d-5(2+6d) | | -12=4(x-8)+32 | | x^(17/3) | | 36=15c | | 22-3x=-4(4x+2)-4(-3-3x) | | X=-5b+12 | | 8(x+62)=10(x+5) | | 29-(-5)=-2x+13-x | | 4+6x=3(2x+3) |